Cultural Inheritance Dynamics in Families and Its Impact on Children's Education in Timor-Leste: A Sociocultural Study - Deus, Alex Coli de; Genda, Arsyad; RAF, Nuvida; Masri, Abd. Rasyid; Mirwan, Mirwan; Wandi, Wandi (Journal Social Civilecial, 2026)
This systematic literature review examines how indigenous cultural inheritance shapes children’s education in Timor-Leste. It analyzes the interaction between customary institutions, language systems, gendered kinship structures, and formal schooling. Data were drawn from academic journals, institutional reports, and scholarly books published between 2000 and 2024. A total of 42 studies were synthesized using thematic analysis. The findings reveal a persistent epistemic misalignment between indigenous knowledge systems and formal education structures. Institutions such as uma lulik, lisan, and tara bandu regulate learning through communal obligation, moral authority, and ritual participation. These systems often conflict with school schedules and institutional expectations, contributing to absenteeism and dropout patterns. Linguistic transition from indigenous mother tongues to Tetum and Portuguese produces an epistemic discontinuity that affects literacy development and classroom engagement. Gendered kinship systems further influence educational access, where household investment decisions favor differentiated roles for boys and girls. Despite these challenges, cultural heritage functions as pedagogical capital that can enhance learning when integrated into formal education. The study argues that educational inequality in Timor-Leste is structurally produced through misalignment between cultural transmission and institutional schooling. It recommends culturally responsive pedagogy, multilingual education strategies, and community-based educational collaboration. These findings contribute to policy debates on educational reform in post-conflict multilingual societies and highlight the importance of integrating indigenous epistemologies within national curriculum frameworks designs.